Morphology development to achieve electrical conductive blends based on polylactic acid/polyolefin elastomer/graphene nanoplates - Z. Saki; H. Azizi; I. Ghasemi; A. Alavi (eXPRESS Polymer Letters)
In the current research, to develop the morphology and improvement of electrical conductivity at low levels of graphene nanoplates (GNPs); the effect of polyolefin elastomer (POE) and graphene content on morphology, mechanical and electrical properties of polylactic acid (PLA) was investigated. Different Blends with and without compatibilizer were prepared via melt mixing process in an internal mixer through masterbatch approach. Co-continuous morphology was obtained at the ratio of 60/40 (wt%/wt%) of PLA/POE. By considering the wetting coefficient, it was predicted that graphene nanoplates have more affinity to the POE phase than PLA, which was confirmed by microscopic observations. The electrical percolation threshold was seen at 0.5–1 wt% of graphene, while the rheological percolation threshold was obtained at 0.2–0.5 wt%. The addition of POE and graphene to PLA led to balancing elongation at break and tensile strength of final products.